Cold-Flow CFD Analysis of Intake-Compression process for Hydrogen-Fuelled Internal Combustion Engine - Amat, Arif Danial (IRC, 2016)
The purpose of this study is to perform a Computational Fluid Dynamics (CFD) simulation to investigate cold flow intake-compression process of a 2D combustion chamber model for a hydrogen fuelled four-stroke internal combustion engine. Commercial CFD codes, ANSYS-Fluent were used for the simulation. The engine speed for the simulation was varied between 1000, 2000 and 3000 RPM with the crank angle between 360 to 720 degree to simulate the intake and compression cycle of the engine. Equivalence ratio of 1, 0.8 and 0.6 were used for all three engine speed. The results of the study includes the effect of engine speed on flow field characteristics (In-cylinder pressure, temperature) as well as equivalence ratio on volumetric efficiency of the engine. The air and fuel mixture flow is represented by the temperature, pressure and velocity magnitude at different engine speed.